(untitled) (The Review of Diabetic Studies, 2025)
The first quarter of the 21st century has been characterized by a "poly-crisis" landscape, where health systems globally face a convergence of biological, climatological, and geopolitical threats. This systematic review comprehensively examines the intersection of health security and healthcare system resilience (HSR), positing that the historical bifurcation of these fields has created critical vulnerabilities in national and international response mechanisms. Drawing upon a diverse array of literature, policy documents, and empirical case studies from 2023 and prior, this report investigates the operational, financial, and sociopolitical determinants that enable health systems to absorb, adapt to, and transform in the face of acute shocks. The analysis reveals that resilience is not merely the ability to bounce back to a pre-crisis state but a dynamic capacity for transformation that must be intentionally programmed into health system functions. Key findings indicate that command-and-control governance, while effective in the early phases of containment (as evidenced in Vietnam), must be balanced with decentralized community engagement (as seen in Kerala, India) to sustain long-term resilience. Furthermore, the review highlights the catastrophic failure of "just-in-time" supply chain efficiency models, advocating for a strategic pivot toward "just-in-case" redundancy and local manufacturing capabilities. Economically, the evidence suggests that investments in resilience yield significant returns, with every dollar invested in preparedness potentially saving exponentially more in response costs, yet financing remains fragmented between vertical security programs and horizontal system strengthening. Ultimately, this report argues for a unified framework where health security is embedded within the fabric of universal health coverage (UHC). It identifies critical research gaps in the measurement of resilience, noting that pre-pandemic indices largely failed to predict actual country performance. The synthesis concludes that future preparedness relies on addressing the "silent" foundations of resilience—workforce well-being, trust capital, and data interoperability—rather than solely focusing on the visible hardware of outbreak response.